Skrift, tale og simulering av andres sansning - Ødemark, John (Tidsskrift for kulturforskning, 2007)
This article examines the so-called sensory turn in cultural studies from the perspective of cultural translation. What are the manuals of translation used in the cultural translation of the sensory cultures of others? I identify two manuals or models that govern translation: (i) the idea of cultural patterns that bridge the relations between cultural part and cultural whole, i.e. a certain organic and aesthetic holism; (ii) the dichotomy between written and oral culture. I argue that the last is too general and the first too reductive to offer viable bridgeheads into the sensory worlds of "others". Furthermore, I argue that a study of sensory culture should account for linguistic, textual and conceptual factors in the process of cultural translation.